PENGARUH KESADARAN PERPAJAKAN, SOSIALISASI PERPAJAKAN, PELAYANAN FISKUS, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Stefani Siahaan; Halimatusyadiah Halimatusyadiah (UNIB Press, 2018)
This research is intended to increase tax awareness, tax socialization, fiscal service, and tax penalties. The data used in this study were primary data. Primary data from questionnaires distributed to Individual Taxpayer in Bengkulu City. The number of questionnaires distributed was 109 questionnaires, but only 104 questionnaires could be processed. Data were analyzed by using multiple linear regression analysis using SPSS program. The results of the research indicate the existence of taxation awareness and tax penalties on positive individual Taxpayer, while the socialization of taxation and fiscal service does not apply to individual taxpayer compliance. This research can contribute for KPP Pratama Kota Bengkulu to improve taxpayer compliance by raising tax awareness and tax penalties. The limitations of this study, researchers only use individual taxpayer respondents who have business activities in the city of Bengkulu. For further research may add an individual Taxpayer who has a free employment or corporate taxpayerKey Words: tax awareness,tax socialization, fiscal service, tax penalties, and personal taxpayer compliance.